EMPATI PERCAYA DIRI BAGI PEMUDA PAPUA DI JAKARTA DALAM PENDEKATAN PERANCANGAN PARA-PARA CENDRAWASIH - Erikson Otniel Indouw; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2023)
Responding to current developments, every community is required to be able to interact and cooperate with others to achieve the ideals of national progress as a whole on the basis of